2019
DOI: 10.1111/soin.12296
|View full text |Cite
|
Sign up to set email alerts
|

Stopping the Hate: Applying Insights on Bullying Victimization to Understand and Reduce the Emergence of Hate in Schools*

Abstract: Scholars and educators study how the school climate influences aggressive behaviors like bullying. Far less research examines the relationship between school climate and hateful actions. This study addresses that gap by examining students' perceptions and observations of the school climate with a nationally representative sample of U.S. middle and high school students. These data include reports of hateful verbal victimization and observations of hateful words and symbols. While some speculate that bullying an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 44 publications
(54 reference statements)
1
43
0
2
Order By: Relevance
“…However, research specifically on the associations between classroom climate and adolescents' engagement in hate speech is scarce. One study found that fair and transparent school rules are negatively linked to hate speech witnessing and victimization in schools (Lehman, 2019). Other research documented that social norms within classrooms favoring hate speech are linked positively to adolescents' hate speech perpetration (Ballaschk et al, 2021;Wachs, Wettstein et al, 2022c, 2022d.…”
Section: Classroom Climate As Contextual Correlate Of Counterspeechmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research specifically on the associations between classroom climate and adolescents' engagement in hate speech is scarce. One study found that fair and transparent school rules are negatively linked to hate speech witnessing and victimization in schools (Lehman, 2019). Other research documented that social norms within classrooms favoring hate speech are linked positively to adolescents' hate speech perpetration (Ballaschk et al, 2021;Wachs, Wettstein et al, 2022c, 2022d.…”
Section: Classroom Climate As Contextual Correlate Of Counterspeechmentioning
confidence: 99%
“…Keywords hate speech, counter speech, empathy, self-efficacy, adolescents Hate speech can be defined as any harmful communicative form of expression that deliberately promotes, justifies, or disseminates hatred or prejudice toward particular social groups and minorities (e.g., LGBTQI+ people, people of color, people with Muslim or Jewish backgrounds, or refugees; Kansok-Dusche et al, 2022). Although hate speech is often discussed as an online phenomenon, it can also be carried out face-to-face (e.g., in schools) and without the use of information and communication technologies (Krause et al, 2021;Lehman, 2019). While current hate speech research involving adolescents has mainly focused on hate speech witnessing, perpetration, and victimization, other forms of involvement, such as countering hate speech (counterspeech), remain blind spots (Kansok-Dusche et al, 2022).…”
mentioning
confidence: 99%
“…Schools are, however, also a place where students experience interpersonal conflicts and victimization, such as hate speech and discrimination. Such experiences pose risks to the personal development of those students involved and the overall school community, thereby reducing the effectiveness of schools’ societal function (Krause et al, 2021; Lehman, 2019, 2020; Thapa et al, 2013).…”
mentioning
confidence: 99%
“…Die Verwobenheit von Hatespeech im Online- und Offline-Kontext steht im Einklang mit Erkenntnissen der Bullying-Forschung, die ebenfalls Zusammenhänge zwischen Offline- und Cyber-Bullying aufzeigen konnte (Wachs und Wolf 2011 ). Für Hatespeech bei Jugendlichen sind solche Verflechtungen ein Forschungsdesiderat, da die bisherige Forschung Hatespeech entweder nur in Schulen (Lehman 2019 , 2020 ) oder ausschließlich digital erforschte (Kansok-Dusche et al. 2022 ).…”
Section: Diskussionunclassified
“… 2022 ). Da Schüler_innen Hatespeech gezielt so einsetzten, dass sie sich der Wahrnehmung von Pädagog_innen entzieht, ist eine positive Beziehung zwischen Schüler_innen und pädagogischen Fachkräften förderlich, da Betroffene das Schulpersonal dann eher in Konflikte einbeziehen (Lehman 2019 ; Tillmann et al. 2007 ).…”
Section: Diskussionunclassified